AplikasiEdible Coatingdari Pati Ubi Jalar Putih pada BuahJambu Air - Sutrisno, Eko; Efendi, Raswen; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aimsto obtain the best starch concentration in the manufacture of edible coatings and the effect of edible coating on the quality and storage time of water apple. This research method used an experimental method, using a completely randomized design (CRD) consisting of six treatments and three replications to obtain 18 experimental units. The treatment in this study is P0 = 0% white sweet potato starch, P1= 1% white sweet potato starch, P2= 2% white sweet potato starch, P3= 3% white sweet potato starch, P4= 4% white sweet potato starch and P5= 5% white sweet potato starch. The parameters observed in edible coating were pH and viscosity, the parameters observed in water apple were weight loss, hardness, total dissolved solids and descriptive sensory tests of flavor, color and texture. Data were analyzed statistically using variance (ANOVA) and (DNMRT) at level 5%. The chosen treatment was at 5% white sweet potato starch concentration with a pH value 3,1 and a viscosity 37867,33 cP on the 12th day with weight loss 9.22%, hardness 1.6 kgf, total solids dissolved 1,669 οbrix. The results of sensory assessment have descriptions of scented water apple, a rather white color, and a rather hard texture. Keywords : Water apple, white sweet potato starch, edible coating.